Penerapan Digital marketing Sebagai Strategi Pemasaran UMKM - NAIMAH, RAHMATUL JANNATIN; WARDHANA, MUHAMMAD WAHYU; HARYANTO, RUDI; PEBRIANTO, AGUS (Jurnal IMPACT: Implementation and Action, 2020)
The Community Service Partner in this activity is Rapi Sari Furniture which engages in the business of producing and buying furniture items. Rapi Sari Meubel is one of the SMEs that has been very long established in the city of Banjarmasin, which is more than 30 years. However, the marketing activities are still very minimal and still conventional. For this reason, training needs to be given on the importance of using digital marketing so that the marketing system can be better, to expand the scope of its business targets and to support better sales activities. In addition, partners are also given assistance in creating accounts in digital media (Google Business and Google) along with how to optimally manage digital media for the promotion of MSME business needs. The resulting outputs are in the form of Google business and Google accounts, scientific articles published in national journals, and activity reports. The method used in thisis activity by provide training in the form of lectures and giving tutorials / practices directly creating accounts in digital media for the MSME.